DAMPAK PENURUNAN SUBSIDI BBM TERHADAP KINERJA SEKTORAL DAN REGIONAL: PENDEKATAN MODEL KESEIMBANGAN UMUM TERAPAN - Budiono Sri Handoko; Y. Sri Susilo (Journal of Indonesian Economy and Business (JIEB), 2000)
The main purpose of this article was to investigate impact of fuel subsidy reduction to sectors/industries and regional in the short run and the long run. Sectors/ industries effect in this case will be looked at from  value added, domestic price, energy price and employment. In this case regional, effect will be looked from aggregate output and employment. This study used INDORANI Applied General Equilibrium Model. Economics Study Inter University Center (Pusat Antar Universitas Studi Ekonomi) Gadjah Mada University with collaboration from IMPACT Project, Monash University, Australia, has been developed INDORANI Applied General Equilibrium Model since early 1997 for Indonesian economy. Data and model of INDORANI has been revised several times. The new version is INDORANI 9571, which is developed from input-output 1995 (I-O 1995). Statistic CenterBoard (Badan Pusat Statistik) produces I-O 1995. In this new version, government sector has been broken-down based on activity type of development sectors. Environment side has been added in the model. With that expansion INDORANI model has extended scope to be used as policy analysis tools. This study used INDORANI 9515 version, which is simplified from INDORANI 9571. INDORANI 9515 aggregates 71 sectors to 15 sectors.  From analysis of simulation result, it could be concluded that fuel subsidy reduction (40%) makes negative impact to sectors/industries and regional in main indicators. From sector side, fuel subsidy reduction causes value added and employment decreasing, increasing of domestic price in almost all-economic sectors. The greater impact can be looked in fuel refinery sector and followed by transportation, medium and big manufacture. In nearest all provinces in Indonesia there were output reduction and employment decreasing because of fuel subsidy reduction. Riau, Southern Sumatra, Eastern Kalimantan gets the greatest impact. The smallest impact reach by DKI Jakarta.